TRANSFORMATION OF SPIRITUAL AND MORAL VALUES OF YOUTH IN THE CONTEXT OF GLOBALIZATION - L. Kozhevnikova; I. Starovoytova; O. Yatsenko (Вестник университета)
The article has been devoted to the study of the impact of new information and communication technologies in the educational environment on the transformation of the values of student youth. It has been shown, how in the process of the evolution of values, a gap occurs between the declared values and life orientations, determining the behavior of young people. The conclusion has been made, that the worldview of modern student youth is of a synthetic nature: it contains, on the one hand, conservative values, focusing on the stability and connection of generations, on the other hand, “modernist” attitudes reflecting modern social realities. It has been shown, that potential opportunities for the inclusion of young people in the innovative development of the country’s economy are determined by the dynamic balance of traditional ethical values and the modern requirements of sociocultural dynamics.